2013
DOI: 10.1007/s11356-013-1681-2
|View full text |Cite
|
Sign up to set email alerts
|

Biogeometallurgical pre-mining characterization of ore deposits: an approach to increase sustainability in the mining process

Abstract: Based on the knowledge obtained from acid mine drainage formation in mine waste environments (tailings impoundments and waste rock dumps), a new methodology is applied to characterize new ore deposits before exploitation starts. This gives the opportunity to design optimized processes for metal recovery of the different mineral assemblages in an ore deposit and at the same time to minimize the environmental impact and costs downstream for mine waste management. Additionally, the whole economic potential is eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Therefore, the time frame proposed in the standard method of 25 cycles (half year or up to one year depending on the length of each cycle), is far too short in order to reach, i.e., predict, acidic conditions in the porphyry copper system. While there is some improvement, i.e., increased oxidation kinetics with new modified cell tests [53,54], they still have to be run for at least 2-3 years, until acid conditions are reached (in case the acid base accounting indicates an excess of acid potential; the usual case for porphyry copper deposits [46]). This increases the costs and time scale for mine waste characterization, which is not very attractive for the mining industry.…”
Section: Evolution Of Post-deposition Geochemical Processes In Tailinmentioning
confidence: 99%
“…Therefore, the time frame proposed in the standard method of 25 cycles (half year or up to one year depending on the length of each cycle), is far too short in order to reach, i.e., predict, acidic conditions in the porphyry copper system. While there is some improvement, i.e., increased oxidation kinetics with new modified cell tests [53,54], they still have to be run for at least 2-3 years, until acid conditions are reached (in case the acid base accounting indicates an excess of acid potential; the usual case for porphyry copper deposits [46]). This increases the costs and time scale for mine waste characterization, which is not very attractive for the mining industry.…”
Section: Evolution Of Post-deposition Geochemical Processes In Tailinmentioning
confidence: 99%
“…In unsaturated zones, microbial-enhanced oxidative dissolution of sulfide minerals is a prime cause of water pollution (Dold and Fontboté, 2001;Johnson and Hallberg, 2003). AMD formation is particularly evident in the case of copper porphyry mine tailings, which typically contain 0.4%-4% sulfur, mainly contained in pyrite (Dold and Weibel, 2013). In arid area such as the Atacama Desert (Peru), metal mobilization by sulfide-oxidizing bacteria result in the transportation toward the tailings surface by evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Sequential acid extraction [27] and the sequential NAG test [14,17] were performed to understand the effects of the sulfur structure on AMD occurrence over time due to varying mineral dissolution rates. Previous studies have shown that sequential extraction is a simple technique to improve AMD prediction precision [18,30,31]. In this study, mineral extraction was performed with HCl, HF, and HNO 3 according to the methods described in [27], where sulfides in abandoned mine tailings were extracted.…”
Section: Experimental Methodsmentioning
confidence: 99%